Rationalität in der Islamischen Theologie II: Die Moderne

Ich habe nur die eine Hälfte genommen – Verstehensprozesse zur Achsensymmetrie - Wallner, Melina (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erkenntnisse aus Arbeitgeberbewertungen: Das Potential von Arbeitsatmosphäre und Arbeitsplatzgestaltung für die Weiterempfehlungsbereitschaft (Studie Industrieverband Büro und Arbeitswelt e. V. (IBA).)

Verification of safety critical control policies using kernel methods - Vertovec, Nikolaus; Ober-Blöbaum, Sina; Margellos, Kostas
Hamilton-Jacobi reachability methods for safety-critical control have been well studied, but the safety guarantees derived rely on the accuracy of the numerical computation. Thus, it is crucial to understand and account for any inaccuracies that occur due to uncertainty in the underlying dynamics and environment as well as the induced numerical errors. To this end, we propose a framework for modeling the error of the value function inherent in Hamilton-Jacobi reachability using a Gaussian process. The derived safety controller can be used in conjuncture with arbitrary controllers to provide a safe hybrid control law. The marginal likelihood of the Gaussian process then provides a confidence metric used to determine switches between a least restrictive controller and a safety controller. We test both the prediction as well as the correction capabilities of the presented method in a classical pursuit-evasion example.

Gottesbilder in den Deuteropaulinen. Metaphernrezeption im Kontext von Bildfeldtraditionen - Taschl-Erber, Andrea (Gottes-Bilder. Zur Metaphorik biblischer Gottesrede (Beiträge zur Wissenschaft vom Alten und Neuen Testament 232))

"Von dem, der getragen wurde durch die Vier und Rettung erfuhr. Ein etwas anderer Blick in die Erzählung von der Heilung des Gelähmten in Mk 2,1-12" - Breuer, Saskia Rebecca (Der Dom. Katholisches Magazin im Erzbistum Paderborn)

Cho, Bernardo K., "Royal Messianism and the Jerusalem Priesthood in the Gospel of Mark" - Breuer, Saskia Rebecca (Theologische Revue)

Teilen und die mediale Logik des Dabei-seins - Bartz, Christina (Following. Ein Kompendium zu Medien der Gefolgschaft und Prozesse des Folgens)

Mensch, Natur, Technik. Miteinander leben, Umwelt und Technik. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Große Fragen. Vergänglichkeit, Werte, Existenz und Welt. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Kultur und Kommunikation. Verständigung und Fantasie. Zyklus 2. - Tenberge, Claudia; von Braunmühl, s

Ich und die anderen. Persönliche Beziehungen. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Ich. Orientierung und Entwicklung. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Brillouin and Raman imaging of domain walls in periodically-poled 5%-MgO:LiNbO3 - Rix, Jan; Rüsing, Michael; Galli, Roberta; Golde, Jonas; Reitzig, Sven; Eng, Lukas M.; Koch, Edmund (Optics Express)
Recently, ferroelectric domain walls (DWs) have attracted considerable attention due to their intrinsic topological effects and their huge potential for optoelectronic applications. In contrast, many of the underlying physical properties and phenomena are not well characterized. In this regard, analyzing the vibrational properties, e.g. by Raman spectroscopy, provides direct access to the various local material properties, such as strains, defects or electric fields. While the optical phonon spectra of DWs have been widely investigated in the past, no reports on the acoustic phonon properties of DWs exist. In this work, we present a joint Raman and Brillouin visualization of ferroelectric DWs in the model ferroelectric lithium niobate. This is possible by using a combined Raman and virtually imaged phased array Brillouin setup. Here, we show that DWs can be visualized via frequency shifts observed in the acoustic phonons, as well. The observed contrast then is qualitatively explained by models adapted from Raman spectroscopy. This work, hence, provides a novel route to study ferroelectric DWs and their intrinsic mechanical properties.
Keywords: Atomic and Molecular Physics; and Optics

Denkschrift - Markewitz, Friedrich; Schuster, Britt-Marie (Im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

Blut - Schuster, Britt-Marie; Wilk, Nicole M. (Im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

CARS Domain-Wall Analysis in single-crystalline Lithium Niobate - Reitzig, Sven; Hempel, Franz; Rüsing, Michael; Eng, Lukas M. (OSA Nonlinear Optics 2021)
We apply coherent anti-Stokes Raman scattering (CARS) for high-speed imaging of domain walls in lithium niobate. The domain wall signature provides similar spectral features as in spontaneous Raman spectroscopy, however at drastically increased scan speeds.

Second-harmonic microscopy in optically confining nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Rüsing, Michael; Eng, Lukas M. (OSA Nonlinear Optics 2021)
The influence of geometrical confinement in back-reflection Second-Harmonic microscopy is experimentally and theoretically investigated in the wedge-shaped model system lithium niobate. The co-propagating signal is found to be the dominating contribution.

Broadband Coherent Anti-Stokes Raman Scattering on Solid State Systems - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (OSA Nonlinear Optics 2021)
We apply broadband coherent anti-Stokes Raman scattering, an imaging tech- nique mostly applied in biology, to the solid state system lithium niobate, where we show an enhanced full spectrum and a working signal transformation.

HPO x ELA: Investigating Hyperparameter Optimization Landscapes by Means of Exploratory Landscape Analysis - Schneider, Lennart; Schäpermeier, Lennart; Prager, Raphael Patrick; Bischl, Bernd; Trautmann, Heike; Kerschke, Pascal (Parallel Problem Solving from Nature — PPSN XVII)
Hyperparameter optimization (HPO) is a key component of machine learning models for achieving peak predictive performance. While numerous methods and algorithms for HPO have been proposed over the last years, little progress has been made in illuminating and examining the actual structure of these black-box optimization problems. Exploratory landscape analysis (ELA) subsumes a set of techniques that can be used to gain knowledge about properties of unknown optimization problems. In this paper, we evaluate the performance of five different black-box optimizers on 30 HPO problems, which consist of two-, three- and five-dimensional continuous search spaces of the XGBoost learner trained on 10 different data sets. This is contrasted with the performance of the same optimizers evaluated on 360 problem instances from the black-box optimization benchmark (BBOB). We then compute ELA features on the HPO and BBOB problems and examine similarities and differences. A cluster analysis of the HPO and BBOB problems in ELA feature space allows us to identify how the HPO problems compare to the BBOB problems on a structural meta-level. We identify a subset of BBOB problems that are close to the HPO problems in ELA feature space and show that optimizer performance is comparably similar on these two sets of benchmark problems. We highlight open challenges of ELA for HPO and discuss potential directions of future research and applications.